Impact of light curing modes on microleakage in alkasite and high viscosity glass ionomer cement restorations - Jian, Sheng Lee; Noor Azlin Yahya, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Light curing modes influence the polymerisation shrinkage of dental materials, and subsequently affect the degree of microleakage generated from the resultant contraction stress. Alkasite and high viscosity glass ionomer cement (HVGIC) are newer light-cured tooth-coloured restorative materials for restoring posterior proximal or Class II cavities. This study investigated the impact of light curing modes and test materials on the microleakage of alkasite Cention N (CN) and Riva Light Cure HVGIC (RV). Twenty sound premolars were randomly segregated into two groups, i.e., Group CN and Group RV. Class II slot cavities of standard dimension (3 mm bucco-lingually, 2 mm mesio-distally and 5 mm occluso-gingivally) were prepared on both proximal surfaces of all teeth, resulting in twenty cavities in each group. Within groups, ten cavities were cured under high power, while the others were cured under soft-start polymerisation. The samples were then thermocycled at 5 °C and 55 °C for 500 cycles before immersion in 0.5% methylene blue dye for 24 h. The samples were sectioned mesio-distally into buccal and lingual halves. Occlusal and cervical microleakage scores were obtained under a stereomicroscope at 100× magnification. Data were analysed using the Mann-Whitney U Test and multinomial logistic regression (p < 0.05). Results showed that the impact of light curing mode on microleakage was insignificant. The majority of CN samples (67.5%) presented no occlusal microleakage (score 0), while RV samples (90%) presented occlusal microleakage up to enamel (score 1). Cervical microleakage was significantly higher than occlusal microleakage for both groups.